Renal replacement therapy in patients affected by Covid-19 in an Intensive Care Unit in the countryside of Rondônia (Research, Society and Development, 2021)
The research was carried out from the analysis of medical records of patients who acquired Acute Kidney Injury (AKI) and needed Kidney Replacement Therapy (RRT) in admissions to Covid Intensive Care Units of the Hospital Regional de Cacoal (HRC) in the countryside of Rondônia . It is a descriptive, cross-sectional, retrospective study with a quantitative approach. After applying the exclusion criteria, 188 medical records were able to be analyzed from June 2020 to June 2021. Of the 188 patients, 108 were male (57%), with a mean age of 62.44, minimum age 23 and maximum 94 years. Diabetes, hypertension and obesity were the most prevalent pre-existing diseases in the study with 84%, and 6% of patients developed AKI without having any declared comorbidity. In this study, there is a high rate of patients who evolved to hemodialysis with a high mortality outcome with altered laboratory tests, totaling 93% of deaths and 7% of discharges. AKI in patients hospitalized with Covid-19 is intertwined with a poor prognosis with a high mortality rate, that the hyperinflammatory state affects the renal cells, causing the need for renal replacement therapy.